2015
DOI: 10.1002/tox.22228
|View full text |Cite
|
Sign up to set email alerts
|

Influence of waterborne gallic and pelargonic acid exposures on biochemical and reproductive parameters in the zebrafish (Danio rerio)

Abstract: Gallic and pelargonic acids are biologically derived substances receiving a growing interest as eco-friendly biocides with potential applications in freshwater system management. However, some data gaps remain to address their chronic ecotoxicity issue, particularly for fish. This work aimed at investigating the sublethal effects of a long-term waterborne exposure of zebrafish to these compounds. Mature fish were exposed to gallic or pelargonic acid at the concentrations of 0, 0.05, 0.5 and 5 mg/L during one m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Few previous studies have examined the toxicity of pelargonic acid to animals. One exception is the work of Techer et al [102,103], who demonstrated lethal and sub lethal toxicity to zebrafish, including LC 50 = 81.2 mg/L, and decreased hormone levels and liver damage at sub lethal concentrations. Our results corroborate the importance of formulation in elucidating herbicide toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Few previous studies have examined the toxicity of pelargonic acid to animals. One exception is the work of Techer et al [102,103], who demonstrated lethal and sub lethal toxicity to zebrafish, including LC 50 = 81.2 mg/L, and decreased hormone levels and liver damage at sub lethal concentrations. Our results corroborate the importance of formulation in elucidating herbicide toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the endocrine disrupting compounds 2,4,6-tribromophenol [31] and bisphenol A [32] increased the accumulation of vitellogenin in oocytes following maternal toxicant exposures in fish species including zebrafish. Others demonstrated that vitellogenin expression in the liver and in circulation is a sensitive biomarker of exposures to toxicants and endocrine disrupting compounds such as: perfluorooctanesulfonic acid [33] (unpublished data), di(2-ethylhexyl) phthalate [34], bisphenol A and tetrabromobisphenol A [33, 35, 36], endosulfan [35], heptachlor and methoxychlor [35], flutamide [37], betulinol [38], and pharmacological agents such as: diethylstilbestrol [37], 17α-ethinylestradiol [39, 40, 36], 17β-trenbolone [40], and gallic and pelargonic acids [41]. The zebrafish embryo provides an excellent model to study vitellogenesis, as fluorescently-labeled vitellogenin can be injected into maternal fish and incorporation into eggs can be quantified [29].…”
Section: Toxicants Affecting Maternal Yolk Depositionmentioning
confidence: 99%
“…When fishes live in the suitable pH range environment, the main enzyme activity in corresponding tissues and organs activity were increased for maintaining the metabolism. 101 The pH value caused by some chemicals beyond the scope can lead to the water content changes, it may even be turned into some toxic substances, affecting the water quality and condition of the dissolved oxygen in the water. 102 If the ion concentration in the water is higher that exceeds the plasma osmotic pressure in the fish, a large amount of salt enters the fish causing water loss in the body and the osmotic pressure increase.…”
Section: Discussionmentioning
confidence: 99%